A Robinsonade or a Story of a Failed Adaptation - Maleszyńska, Joanna (Porównania, 2019)
The article discusses Jacques Offenbach’s operetta Robinson Crusoe, whose libretto is based on the great 1719 novel by Daniel Defoe by the same title. The adaptation by French librettists in the late 19th century is a far cry from the original narrative. The novel, an epic hymn to human resourcefulness and resilience, became a light comedy with a trite story line and without a deeper message. The analysis of two formally very different texts with the same protagonist brings about a conclusion of an innate impossibility of translating a grand novel to a comedy stage.